Presenting with Impact: Training Students' Oral Presentation Skills - Jusuf Blegur; Isak Riwu Rohi; Yahya J. Palinata; Fredik E. Nope; Andreas J. F. Lumba; Ramona M. Mae; Christin P. M. Rajagukguk (GANDRUNG: Jurnal Pengabdian Kepada Masyarakat, 2023)
Oral presentations have become pivotal in recent learning. Students must communicate their work or experiments to colleagues and lecturers through scientific protocols. In many cases, it was detected that students often experienced difficulties making oral presentations, resulting in irritation in critical and constructive class discussions. This service aims to conduct presenting with impact training to train students' oral presentations using lecture and discussion methods, exercises and peer-reviews, and oral presentations. Participants involved as many as 16 people. As a result, there was an increase in the participants' oral presentation skills in terms of content accuracy, effective communication, and clarity of speech. However, it still needs to improve various indicators to characterize oral presentation skills in various conditions. Presentation training should be a regular agenda to equip students with the latest oral presentation instruments to strengthen their professional skill profile as prospective teachers.